The Influence of Cultural Literacy on the Students’ Accommodative Attitudes Towards Religious Moderation and Local Culture Preservation at Ma’had al-Jami’ah of State Islamic University (PTKIN) - Fatihunnada, Fatihunnada; Ruswandi, Bambang; Suhail, Ahmad Kusjairi; Oktaviano, Willy; Larhzizer, Fouad (Millati: Journal of Islamic Studies and Humanities, 2025)
This study examines the level of cultural literacy among the students of Ma’had al-Jami’ah at PTKIN as an indicator for assessing perspectives and attitudes related to religious moderation, particularly in terms of accommodative attitudes towards local culture. Previous studies on the influence of literacy on religious moderation present mixed findings. Mahmudah and Handayani emphasize a significant correlation between literacy levels and religious moderation, while Wulan argues the opposite. This research employs a quota sampling method. The population consists of Ma’had al-Jami’ah students from four institutions: UIN Syarif Hidayatullah Jakarta, UIN Sunang Gunung Djati Bandung, UIN Walisongo Semarang, and UIN Maulana Malik Ibrahim Malang, with a total sample of 365 students. The findings reveal a very high level of cultural literacy among the students, with a score of 100 on the scale and an index of 83.03%. This was assessed based on three cultural literacy indicators. There are religiosity values (88.59%), cultural sensitivity (86.67%) and intercultural interaction (76.01%). The accommodative attitudes towards local culture were measured at 79.33%. Hypothesis testing indicates that cultural literacy has a significant impact on accommodative attitudes towards local culture, with a coefficient of 0.4665 or 32.28%. The results suggest that the higher the level of cultural literacy, the stronger the students’ religious moderation.